Growth Patterns of Residual Tumor in Preoperatively Growing Vestibular Schwannomas - Kasbekar, Anand V.; Adan, Guleed H.; Beacall, Alaina; Youssef, Ahmed M.; Gilkes, Catherine E.; Lesser, Tristram H. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives To analyze growth of residual vestibular schwannoma (VS) following incomplete tumor resection and determine the influence of residual location and size.Design Retrospective case note and scan review.Setting Tertiary skull base unit.Participants Patients with residual tumor following primary surgery for medium and large unilateral growing vestibular schwanomas between 2006 and 2009.Main Outcome Measures Location of residual VS and post-operative growth, comparing those with more (>5%) or less than 5% of tumor residual (<5%).Results Fifty-two patients had visible residual tumor left behind at surgery. Twenty had < 5% and 32 had > 5% residual. The residual growth rates were 38% overall, 20% in < 5%, and 50% in > 5% residuals. There was no significant difference in growth rates at different residual locations. Median follow-up was 6.4 years.Conclusions There is a greater risk of regrowth of residuals > 5%. All positions of residual tumor can regrow, and the preoperative tumor size plays a role in this. Further data is needed to confirm if residual tumor in the fundus is less likely to grow.
Keywords: vestibular schwannoma; residual tumor; tumor regrowth